ENVIRONMENTAL COMMUNICATION ON INSTAGRAM OF DKI JAKARTA ENVIRONTMENTAL AGENCY (DINAS LINGKUNGAN HIDUP DKI JAKARTA) - Taufiqulhakim, Ferdio Rizqi; Dirgantara, Pradipta (eProceedings of Management, 2025)
The research objective is to find out how the environmental communication is applied on the Instagram account ofDLH DKI Jakarta. Jakarta faces various environmental problems such as air pollution, flooding, and suboptimal wastemanagement. The DKI Jakarta Environmental Agency (DLH) as a government institution utilizes Instagram as amedium to disseminate information and raise public awareness about environmental issues. This study aims to explorehow environmental communication is conducted by DLH DKI Jakarta through Instagram in addressing environmentalproblems. The research uses a qualitative approach with an instrumental case study type and constructivist paradigm.Data were collected through in-depth interviews, observation, and documentation. The analysis refers to Foulger(2004) Ecological Model of the Communication Process, which includes elements such as message creators, media,language, audience feedback, and the relationship between sender and receiver. The findings show that DLH DKIJakarta applies a structured and adaptive communication strategy through visual and educational content, with twoway interaction between the agency and the public. The study concludes that social media, especially Instagram, canserve a communication tool to build public awareness and participation in environmental issues.Keywords: Environmental communication, Instagram, Environmental Agency, Jakarta, Social Media